Hungarian Monitoring, 28 March 1989 . [Magyar rádiófigyelő], 1989. március 28 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - More demonstrations and disturbances in Kosovo - First Soviet alternative elections - Bush administration's ideas on a new Eastern European settlement plan with the USSR - Franco's troops entered Madrid 50 years ago Domestic Affairs: - Politicians receive American parliamentary delegation - South Korean foreign minister in talks in Budapest - Conversation about the work of correspondents - Signatures collected against Transylvanian refugees' camp - Hungarian-Romanian friendship society calls for peace between the two peoples - Smallholders letter to the justice minister - Show trials of the 1940s and 1950s to be re-examined Economy: - USD 600 million gap in Hungarian wages at the end of March Külpolitika: - Koszovóban folytatódnak a tüntetések, zavargások - Az első szovjet alternatív választásról - A Bush-kormányzat elképzelései egy újfajta kelet-európai berendezkedés tervével a SZU-val kapcsolatban - 50 évvel ezelőtt vonultak be Madridba Franco csapatai Belpolitika: - Politikusok fogadják az amerikai parlamenti küldöttséget - Budapesten tárgyal a dél-koreai külügyminiszter - Beszélgetés a tudósítók munkájáról - Aláírásgyűjtés egy erdélyi menekülttábor ellen - Egy magyar - Román baráti kör a két nép közötti megbékélésre szólít fel - A Kisgazdapárt levele az igazságügy miniszterhez - Felülvizsgálatra kerülnek a 4o-5o-es évek koncepciós perei Gazdaság: - A magyar fizetési mérleg hiánya március végén 6oo millió dollár